DEPORTASI ANAK DALAM KONFLIK RUSIA–UKRAINA: ANALISIS PERTANGGUNGJAWABAN HUKUM SEBAGAI KEJAHATAN PERANG - Yoal, Levis (Universitas Labuhanbatu, 2025)
This study examines the legal accountability for the deportation of children in the Russia–Ukraine armed conflict, which has been recognized as a war crime under international law. Reports indicate that 16,000 to 19,000 Ukrainian children have been forcibly deported to Russia. Using a doctrinal legal method with a statute and literature approach, this research analyzes the responsibility of both the state and individuals. At the state level, accountability is based on the Geneva Convention IV of 1949 and the Articles on Responsibility of States for Internationally Wrongful Acts, which obligate states to provide restitution, compensation, or satisfaction for internationally wrongful acts. Sanctions imposed by other states may include trade embargoes, investment restrictions, and asset freezes. At the individual level, international criminal law, particularly Article 25 of the Rome Statute, holds leaders personally accountable for direct or indirect involvement in war crimes, as exemplified in past prosecutions of Omar Al-Bashir, Slobodan Milosevic, and Jean Paul Akayesu. The findings emphasize that deportation of children in the Russia–Ukraine conflict constitutes both state and individual responsibility, requiring effective international enforcement to ensure justice and deterrence.Keywords: Child Deportation; Individual Responsibility; State Responsibility; Russia–Ukraine